Bio‐fabricated chromium (III) oxide nanorods for catalytic and bactericidal applications in water treatment. Issue 9 (4th August 2022) - Bukhari, Syeda Farah; Ali, Syed Nawazish; Dildar, Nazish; Tauseef, Saima; Khan, Salman Tariq; Sara,; Zia, Ambreen; Hasan, Erum; Ali, Sundus; Shehzadi, Mehreen
Abstract: The treatment of chemical and biological contaminants in water through bio‐fabricated metal nanoparticles is one of the promising sustainable methods. Herein, an efficient synthesis of novel chromium oxide nanorods is introduced by Illicium verum fruit extract as a bio‐reducing, capping, and stabilizing agent. The morphological, optical, catalytic, and bactericidal properties of nanorods are investigated by various techniques. The UV–visible spectra displayed strong absorption peak in the region of 309.8 nm, whereas Fourier transform infrared presented the characteristic vibrations at 605.65 and 651.94 cm −1 attributed to CrO binding mode. Scanning electron microscopy results showed that chromium oxide nanoparticles are well‐dispersed with small rod‐shaped morphology. The average size of nanorods was found to be 15 to 20 nm in length. Due to their ultra‐large surface area and strong π–π interaction, the plant‐coated nanorods were tested for the catalytic removal of methyl orange (MO), a common water‐soluble textile dye. Adsorption potential of Cr2 O3 nanoparticles was monitored by UV–visible spectrophotometer, which showed 90–95% successive decrease in the absorption maxima of aqueous MO (1 μM). The elimination rate of MO was drastically improved from 45 to 30 min, while a combination of Cr2 O3 nanorods and sodium borohydride NaBH4 was used. Bactericidal activities of these nanorods were tested against vast number of Gram‐positive and Gram‐negative bacteria. The significant results were obtained with 27 mm zone of inhibition against Klebsiella . oxytoca and Serratia . marcescens . This quick and simple procedure can be scaled up for commercial applications of new, eco‐friendly, and cost‐effective water treatment process. Abstract : In this work, the novel strategy for using Illicium . verum fruit extract to fabricate Cr2 O3 nanorods and examining the nanorod activities in methyl orange degradation and antibacterial application is described. The results reveal that the utilization of Cr2 O3 nanorods does enhance both kinds of activities. Overall, this manuscript provides a novel idea to synthesize uniform Cr2 O3 nanorods.